2010
DOI: 10.4067/s0716-97602010000100013
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Cassia fistula Linn. on diethylnitrosamine induced hepatocellular damage and oxidative stress in ethanol pretreated rats

Abstract: Diethylnitrosamine (DEN), found in many commonly consumed foods, is widely reported to induce cancer in animals and humans. The aim of the present study was to investigate the hepatoprotective and antioxidant activities of the leaf extract of the medicinal plant Cassia fistula Linn. against diethylnitrosamine induced liver injury in ethanol pretreated rats. Albino Wistar rats, pretreated with ethanol for 15 days, were administered a single dose of DEN. Thirty days after DEN administration, hepatotocellular dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 39 publications
9
19
0
Order By: Relevance
“…It is not easy to define a profile pattern of antioxidant expression in tumor cells, but it is admissible that the increased number of abnormal cell population may lead to antioxidant gene expression deregulation without any meaning in antioxidant defense. The decreased content of GSH and dependent enzymes -GST and GR -in DEN exposed mice after T2 may support the idea that hepatocellular damage influences antioxidant gene expression; supporting results were also described by Pradeep et al (2010).…”
Section: Discussionsupporting
confidence: 77%
“…It is not easy to define a profile pattern of antioxidant expression in tumor cells, but it is admissible that the increased number of abnormal cell population may lead to antioxidant gene expression deregulation without any meaning in antioxidant defense. The decreased content of GSH and dependent enzymes -GST and GR -in DEN exposed mice after T2 may support the idea that hepatocellular damage influences antioxidant gene expression; supporting results were also described by Pradeep et al (2010).…”
Section: Discussionsupporting
confidence: 77%
“…Our result agrees well with that [33][34] who reported that elevated levels of serum AST, ALT, ALP, LDH and γ-GT, and simultaneous fall in the levels of the marker enzymes in the liver tissue induced by DEN was altered after the administration of ethanolic leaf extract of the medicinal plant Cassia fistula Linn. The structural integrity of the cells has been damaged in cancer induced animals, and this results in cytoplasmic leakage of the enzyme into the blood stream, leads to the elevated levels of these enzymes in blood with a subsequent fall in the tissues [35].…”
Section: Resultssupporting
confidence: 83%
“…It is reported that DEN cause oxidative stress during the metabolism that lead to cytotoxicity, mutagenicity and carcinogenicity (3,4). DEN is biotransformed by mixed-function cytochrome P450 dependent monooxidase systems and its metabolic activation is responsible for the onset of the toxic effects (5). So the use of antioxidants offer to protect this deleterious effects.…”
Section: Introductionmentioning
confidence: 99%